Branched Peptide, B2088, Disrupts the Supramolecular Organization of Lipopolysaccharides and Sensitizes the Gram-negative Bacteria - Lakshminarayanan, Rajamani (2016)
Dissecting the complexities of branched peptide-lipopolysaccharides (LPS) interactions provide rationale for the development of non-cytotoxic antibiotic adjuvants. Using various biophysical methods, we show that the branched peptide, B2088, binds to lipid A and disrupts the supramolecular organization of LPS. The disruption of outer membrane in an intact bacterium was demonstrated by fluorescence spectroscopy and checkerboard assays, the latter confirming strong to moderate synergism between B2088 and various classes of antibiotics. The potency of synergistic combinations of B2088 and antibiotics was further established by time-kill kinetics, mammalian cell culture infections model and in vivo model of bacterial keratitis. Importantly, B2088 did not show any cytotoxicity to corneal epithelial cells for at least 96 h continuous exposure or hemolytic activity even at 20 mg/ml. Peptide congeners containing norvaline, phenylalanine and tyrosine (instead of valine in B2088) displayed better synergism compared to other substitutions. We propose that high affinity and subsequent disruption of the supramolecular assembly of LPS by the branched peptides are vital for the development of non-cytotoxic antibiotic adjuvants that can enhance the accessibility of conventional antibiotics to the intracellular targets, decrease the antibiotic consumption and holds promise in averting antibiotic resistance.